Hydroxytyrosol linoleoyl ether ameliorates metabolic-associated fatty liver disease symptoms in obese Zucker rats - Tovar, Rubén; De Ceglia, Marialuisa; Rodríguez-Pozo, Miguel; Vargas, Antonio; Gavito, Ana; Suárez, Juan; Boronat, Anna; De la Torre, Rafael; Rodriguez-de-Fonseca, Fernando; Baixeras-Llano, Elena; Decara, Juan (American Chemical Society, 2024)
A main hepatic consequence of obesity is metabolic-associated fatty liver disease (MAFLD), currently treated by improving eating habits and administrating fibrates yet often yielding suboptimal outcomes. Searching for a new therapeutic approach, we aimed to evaluate the efficacy of hydroxytyrosol linoleoyl ether (HTLE), a dual Ppar-α agonist/Cb1 antagonist with inherent antioxidant properties, as an antisteatotic agent. Using lean and obese Zucker rats, they were administrated daily doses of HTLE (3 mg/kg) over a 15-day period, evaluating its safety profile, pharmacokinetics, impact on body weight, hepatic fat content, expression of key enzymes involved in lipogenesis/fatty acid oxidation, and antioxidant capacity. HTLE decreased the body weight and food intake in both rat genotypes. Biochemical analysis demonstrated a favorable safety profile for HTLE along with decreased concentrations of urea, total cholesterol, and aspartate aminotransferase AST transaminases in plasma. Notably, HTLE exhibited potent antisteatotic effects in obese rats, evidenced by a decrease in liver fat content and downregulation of lipogenesis-related enzymes, alongside increased expression of proteins controlling lipid oxidation. Moreover, HTLE successfully counteracted the redox imbalance associated with MAFLD in obese rats, attenuating lipid peroxidation and replenishing both glutathione levels and the overall antioxidant. Our findings highlight the effectiveness of triple-action strategies in managing MAFLD effectively. Based on our results in the Zucker rat model, HTLE emerges as a promising candidate with triple functionality as an anorexigenic, antisteatotic, and antioxidant agent, offering potential relief from MAFLD symptoms associated with obesity while exhibiting minimal side effects. In conclusion, our study positions HTLE as a highly promising compound for therapeutic intervention in MAFLD treatment, warranting further exploration in clinical trials.
Keywords: Ppar-α; Anatomía; Genética; Lípidos; Péptidos; Proteínas; Roedores; HTLE; MAFLD; Zucker rats; Cb1; Antioxidant; Antisteatotic; Ppar-α